Antinociceptive action of isolated mitragynine from Mitragyna speciosa through activation of opioid receptor system - Abdul Rahman, Shamima; Fakurazi, Sharida; Baharuldin, Mohamad Taufik Hidayat; Ithnin, Hairuszah; Mohd Moklas, Mohamad Aris; Palanisamy, Arulselvan (MDPI, 2012)
Cannabinoids and opioids systems share numerous pharmacological properties and antinociception is one of them. Previous findings have shown that mitragynine (MG), a major indole alkaloid found in Mitragyna speciosa (MS) can exert its antinociceptive effects through the opioids system. In the present study, the action of MG was investigated as the antinociceptive agent acting on Cannabinoid receptor type 1 (CB1) and effects on the opioids receptor. The latency time was recorded until the mice showed pain responses such as shaking, licking or jumping and the duration of latency was measured for 2 h at every 15 min interval by hot plate analysis. To investigate the beneficial effects of MG as antinociceptive agent, it was administered intraperitoneally 15 min prior to pain induction with a single dosage (3, 10, 15, 30, and 35 mg/kg b.wt). In this investigation, 35 mg/kg of MG showed significant increase in the latency time and this dosage was used in the antagonist receptor study. The treated groups were administered with AM251 (cannabinoid receptor-1 antagonist), naloxone (non-selective opioid antagonist), naltrindole (δ-opioid antagonist) naloxonazine (µ1-receptor antagonist) and norbinaltorpimine (κ-opioid antagonist) respectively, prior to administration of MG (35 mg/kg). The results showed that the antinociceptive effect of MG was not antagonized by AM251; naloxone and naltrindole were effectively blocked; and norbinaltorpimine partially blocked the antinociceptive effect of MG. Naloxonazine did inhibit the effect of MG, but it was not statistically significant. These results demonstrate that CB1 does not directly have a role in the antinociceptive action of MG where the effect was observed with the activation of opioid receptor.